Emotional context modulates embodied metaphor comprehension. (November 2015) - Samur, Dalya; Lai, Vicky T.; Hagoort, Peter; Willems, Roel M.
Abstract: Emotions are often expressed metaphorically, and both emotion and metaphor are ways through which abstract meaning can be grounded in language. Here we investigate specifically whether motion-related verbs when used metaphorically are differentially sensitive to a preceding emotional context, as compared to when they are used in a literal manner. Participants read stories that ended with ambiguous action/motion sentences (e.g., he got it ), in which the action/motion could be interpreted metaphorically (he understood the idea) or literally (he caught the ball) depending on the preceding story. Orthogonal to the metaphorical manipulation, the stories were high or low in emotional content. The results showed that emotional context modulated the neural response in visual motion areas to the metaphorical interpretation of the sentences, but not to their literal interpretations. In addition, literal interpretations of the target sentences led to stronger activation in the visual motion areas as compared to metaphorical readings of the sentences. We interpret our results as suggesting that emotional context specifically modulates mental simulation during metaphor processing. Highlights: Preceding discourse rendered motion-related target sentences metaphorical or literal. Preceding context was high or low in emotional content. Activation in visual motion area is modulated by context for metaphorical sentences. The effect of emotion on sensory simulation reflects the link between metaphor and emotion.